PENGARUH LEVERAGE, KEPELIMIKAN INSTITUSONAL, UKURAN PERUSAHAAN, DAN PROFITABILITAS TERHADAP PENGHINDARAN PAJAK (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2012-2014) - Ulfa Jasmine; Zirman '; Sem Paulus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study was to examine the effect of leverage, ownership, company size, and profitability against tax avoidance. The population in this study are all manufacturing companies listed in Indonesia Stock Exchange 2012-2014. Sample of companies used in this study as many as 34 companies. While the data processed in this study as many as 102 of data where the data obtained from three consecutive terms (2012-2014) of each of these companies. Data analysis technique used is multiple regression analysis were processed with SPSS Windows 19. The results show that leverage the t (5.617)> t table (1.984) and significant (0.009) <(0.05), ownership institusional that t arithmetic (7.365)> t table (1.984) and significant (0.000) <(0.05), company size t (6.092)> t table (1.984) and significant (0.000) <(0.05), profitability t count (4,207)> t table (1.984) and significant (0.006) <(0.05). Overall, leverage, institusonal ownership, size and profitability affect tax avoidance amounting to 85.2%. While 14.8% is influenced by other variables not examined in this study.Keywords: leverage, ownership,size, profitability and avoidance.